Correlation of the 48bp VNTR locus of DRN4 gene with overweight/obesity (literature review) - E. A. Novikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Obesity is one of the five global health risks; it is a worldwide problem. Mortality of obesity is 2.6 million per year. Recently, obesity is considered as a neurobehavioural disorder with defects appetite control. The central dopamine system regulates eating behavior. The cause of obesity is the diminished dopaminergic neurotransmission, which provokes an increase of food stimulus that leads to an increasing of the body mass index (BM1). 1n this case, the main candidate genes will be genes of dopamine type 2 receptors: dopamine receptor D2 (DRD2), D3 (DRD), D4 (DRD4). The article focuses on the DRD4 gene. The latest literature data about the relationship of various polymorphic variants of the DRD4 gene with eating disorders, overweight and obesity are analyzed. 1t has been clarified, that the 48bp VNTR is the main and most significant polymorphism. One part of the researches shows a positive correlation of the tandem repeat VNTR DRN4 gene with overweight, obesity, eating disorders, including the DRD4-S and DRD4-L alleles. The other part denies the correlation of the tandem repeat VNTR DRN4 gene with these indicators. Perhaps the contradictions are due to differences in research design, as well as ethnic, gender and age differences in cohorts, and due to the fact, that in vitro changes do not always correspond to changes in vivo.